Google Review as Digital Teaching Media for English Writing Skill - Octaviani, Saly Kurnia; Arumsari, Arumsari; Wijayanto, Hendro (Journal of English Language and Education, 2023)
Teachers as facilitator need to find creative teaching media for English writing skills. Students tend to have difficulty to write in English language, especially for hotel and cruise ship students. One of the reasons is students didn’t have any view and interest to build idea and didn’t have enough English vocabulary. Therefore, researchers try to present and explain that Google Review can be a digital teaching media to help educators teaching students in English writing skill about descriptive text. This study explains about feature introduction, application procedure, and teaching strategy. This study used descriptive qualitative method. To collect the data, this study used observation, interview, and literature review. In conclusion, Google Review is flexible and interesting teaching media that allow students to write and describe tourist place based on their own feeling, taste, thought, and experience.